Mental nerve paraesthesia: A review of causes and two endodontically related cases - Unni Krishnan; Alex J Moule (Wolters Kluwer Medknow Publications, 2015)
Mental nerve paraesthesia can occur as a result of a variety of reasons. Paraesthesia following endodontic treatment is an uncommon treatment complication. Causes of paraesthesia in the mental nerve region are reviewed and two cases involving endodontic treatment are discussed. In the first instance, a patient presented with difficulty in swallowing and severe pain localized to her right mandible, with numbness of her lower lip. Paraesthesia resolved quickly with endodontic treatment. In the second instance, a patient referred for treatment a mandibular second premolar developed profound paraesthesia in the distribution of the mental nerve after treatment. The local anesthetic used was 4% articaine by infiltration. CBCT imaging revealed two accessory mental foramen and slight extrusion of sealant into one of the neurovascular exits. Possible causes of paraesthesia are discussed in the light of the literature review. CBCT imaging may be useful in the diagnosis and management of these conditions.